Baseline plasma fatty acids profile and incident cardiovascular events in the SU.FOL.OM3 trial: the evidence revisited. - Léopold K Fezeu; François Laporte; Emmanuelle Kesse-Guyot; Valentina A Andreeva; Jacques Blacher; Serge Hercberg; Pilar Galan (PLoS ONE)
Objective We aimed to investigate the association between baseline plasma fatty acids profile and the risk of future major cardiovascular events in patients with a history of ischaemic heart disease or ischemic stroke. Methods Baseline plasma fatty acids as well as established cardiovascular risk factors were measured in 2,263 patients enrolled in the SUpplementation with FOLate, vitamins B-6 and B-12 and/or OMega-3 fatty acids randomized controlled trial. Incident major cardiovascular, cardiac and cerebrovascular events were ascertained during the 4.7 years of follow up. Hazard ratios were obtained from Cox proportional hazards models after adjustment for cardiovascular risk factors. Results During the follow-up, 154, 379 and 84 patients had major cardiovascular, cardiac and cerebrovascular events respectively. Upon adjustment for gender, initial event, baseline age and BMI, the risk of developing a major cardiovascular event decreased significantly in successive quartiles of arachidonic acid (P trend<0.002), total omega 3 polyunsaturated fatty acids (P trend<0.03), docosapentaenoic acid (P trend<0.019), docosahexaenoic acid (P trend<0.004), eicosapentaenoic acid + docosahexaenoic acid (P trend<0.03) and eicosapentaenoic acid + docosapentaenoic acid + docosahexaenoic acid (P trend<0.02). This inverse association was borderline significant with increased quartiles of stearidonic acid (P trend<0.06). In the full model, only stearidonic acid remained inversely associated with the risk of developing a major cardiovascular event (P trend<0.035), a cardiac event (P trend<0.016) or a cerebrovascular event (P trend<0.014), while arachidonic acid was inversely associated with the risk a cerebrovascular event (P trend<0.033). Conclusion The inverse association of long chain omega 3 polyunsaturated fatty acids with recurrence of Cardiovascular diseases was mainly driven by well-known cardiovascular risk factors. Trial registration Controlled-Trials.com ISRCTN41926726.